Performance of steel beams strengthened with pultruded CFRP plate under various exposures - Gholami, M. (Techno Press, 2016)
The use of Carbon Fiber Reinforced Polymer (CFRP) to strengthen steel structures has attracted the attention of researchers greatly. Previous studies demonstrated bonding of CFRP plates to the steel sections has been a successful method to increase the mechanical properties. However, the main limitation to popular use of steel/CFRP strengthening system is the concern on durability of bonding between steel and CFRP in various environmental conditions. The paper evaluates the performance of I-section steel beams strengthened with pultruded CFRP plate on the bottom flange after exposure to diverse conditions including natural tropical climate, wet/dry cycles, plain water, salt water and acidic solution. Four-point bending tests were performed at specific intervals and the mechanical properties were compared to the control beam. Besides, the ductility of the strengthened beams and distribution of shear stress in adhesive layer were investigated thoroughly. The study found the adhesive layer was the critical part and the performance of the system related directly to its behavior. The highest strength degradation was observed for the beams immersed in salt water around 18% after 8 months exposure. Besides, the ductility of all strengthened beams increased after exposure. A theoretical procedure was employed to model the degradation of epoxy adhesive